دور القاضي الإداري في خلق القاعدة القانونية - محمد نواصرية (My University, 2023)
Summary: The administrative judiciary plays a major role for administrative law, as it is not limited to the mere application of legal texts or the interpretation of ambiguity surrounding them, but also plays a more serious and bolder role in the field of making the legal base in itself in the absence of a legislative text and a lack of legislation, unlike the traditional function of the ordinary judiciary. The reason for granting the administrative judge this authority is the special nature of the rules of administrative law, in terms of its non-codification and the circumstances of its inception and the multiplicity of its fields of activity, which led to the administrative judiciary exceeding the role of the ordinary judiciary to be in line with the requirements of administrative life, and thus its role often exceeds legislation, which led to disagreement about the nature of legal rules and comparing them with legislation, and in the journey of his manufacture of the legal base, the administrative judge follows gradual steps and stages, using sources that help him in this process, the source may be From which the administrative judge derives the judicial rule exists so that it falls within positive law, and this may be derived through the essence of the law. Considering the provisions of article 152 of the Constitution, which stipulates that the Supreme Court and the Council of State guarantee the uniformity of jurisprudence throughout the country and ensure respect for the law, this has been embodied through a set of practical applications of jurisprudence in the administrative article of these bodies in the field of decisions, contracts and administrative responsibility. ................................... ملخص المذكرة: يلعب القضاء الاداري دورا كبير بالنسبة للقانون الإداري، فهو لا يقتصر فقط على مجرد تطبيق النصوص القانونية أو تفسير الغموض الذي يكتنفها، بل يؤدي دور أكثر جدية وأكثر جرأة في مجال صناعة القاعدة القانونية في ذاتها في حالة انعدام النص التشريعي وحالة نقص في التشريع خلافا للوظيفة التقليدية للقضاء العادي. ومرد منح القاضي الإداري هذه السلطة هي الطبيعة الخاصة لقواعد القانون الإداري، من حيث عدم تقنينه وظروف نشأته وتعدد مجالات نشاطه، أدى إلى أن يتجـاوز القضـاء الإداري دور القضـاء العـادي ليتماشى مع متطلبات الحياة الإدارية،ويتعـدى بذلك دوره التشريع في كثير من الأحيان، الامر الذي أدى للاختلاف حول طبيعة القواعد القانونية ومقارنتها بالتشريع، وفي رحلة صناعته للقاعدة القانونية يتبع القاضي الاداري خطوات ومراحل تدريجية مستعينا في ذلك بمصادر تساعده في هذه العملية، فقد يكون المصدر الذي يستقي منه القاضي الإداري القاعدة القضائية موجود بحيث يندرج ضمن القانون الوضعي، وقد يستقي ذلك من خلال جوهر القانون. وبإعتبار ما جاء في أحكام المادة 152 من الدستور التي تنص أن المحكمة العليا ومجلس الدولة يضمنان توحيد الاجتهاد القضائي في جميع أنحاء البلاد ويسهران على احترام القانون، فقد تجسد هذا الامر من خلال مجموعة من التطبيقات العملية للاجتهادات القضائية في المادة الإدارية لهذه الجهات في مجال القرارات والعقود والمسؤولية الإدارية. .................................. Résumé : Le pouvoir judiciaire administratif joue un rôle majeur par rapport au droit administratif, car il ne se limite pas à la simple application des textes juridiques ou à l’interprétation de l’ambiguïté qui les entoure, mais joue également un rôle plus sérieux et plus audacieux dans le domaine de la création de la base juridique elle-même en l’absence de texte législatif et en l’absence de législation, contrairement à la fonction traditionnelle du pouvoir judiciaire ordinaire. La raison pour laquelle le juge administratif accorde cette autorité est la nature particulière des règles de droit administratif, en termes de non-codification et les circonstances de sa création et la multiplicité de ses domaines d’activité, ce qui a conduit le pouvoir judiciaire administratif à dépasser le rôle du pouvoir judiciaire ordinaire pour être conforme aux exigences de la vie administrative, et donc son rôle dépasse souvent la législation, ce qui a conduit à un désaccord sur la nature des règles juridiques et à les comparer avec la législation, et dans le parcours de sa fabrication de la base juridique, le juge administratif suit des étapes et des étapes progressives, en utilisant des sources qui l’aident dans ce processus, la source peut être D’où le juge administratif tire la règle judiciaire existe de sorte qu’elle relève du droit positif, et cela peut être dérivé de l’essence du droit. Compte tenu des dispositions de l’article 152 de la Constitution, qui stipule que la Cour suprême et le Conseil d’État garantissent l’uniformité de la jurisprudence dans tout le pays et assurent le respect de la loi, cela s’est traduit par un ensemble d’applications pratiques de la jurisprudence dans l’article administratif de ces organes dans le domaine des décisions, des contrats et de la responsabilité administrative.